Thymidylate Synthase and Folyl-polyglutamate synthase (FPGS) Are Not Clinically Useful Markers of Response to Pemetrexed [Pem] in Patients with Malignant Pleural Mesothelioma [MPM] - Schwed Lustgarten, Daniel E. (2013)
PURPOSE: Thymidylate synthase (TS) is a potential predictor of outcome after pemetrexed (Pem) in patients with malignant pleural mesothelioma (MPM), and assays measuring TS levels are commercially marketed. The goal of this study was to further evaluate the value of TS and to study another potential biomarker of response, the enzyme, folyl-polyglutamate synthase (FPGS), which activates Pem intracellularly. PATIENTS AND METHODS: Levels of TS and FPGS were semi-quantitatively determined immunohistochemically using H-scores on tissue samples from 85 MPM patients receiving Pem as primary therapy. H-score was correlated with radiographic disease control rate (DCR), time to progression (TTP) and overall survival (OS). In addition, expression levels of TS and FPGS in MPM cell lines were determined using immunoblotting and correlated with their sensitivity to Pem-induced cell death. RESULTS: H-scores from patients with disease control versus progressive disease showed extensive overlap. There were no significant correlations of DCR, TTP, or OS to either TS levels (p = 0.73, 0.93, and 0.59, respectively), FPGS levels (p = 0.95, 0.77 and 0.43 respectively) or the ratio of FPGS/TS using the median scores of each test as cutoffs. There was no correlation between TS or FPGS expression and chemosensitivity of mesothelioma cells to Pem in vitro. CONCLUSIONS: Although previous retrospective data suggest that TS and FPGS expression might be potential markers of Pem efficacy in MPM, our data indicate these markers lack sufficient predictive value in individual patients and should not be used to guide therapeutic decisions in the absence of prospective studies.